2011
DOI: 10.5201/ipol.2011.lmps_rpe
|View full text |Cite
|
Sign up to set email alerts
|

Retinex Poisson Equation: a Model for Color Perception

Abstract: In 1964 Edwin H. Land formulated the Retinex theory, the first attempt to simulate and explain how the human visual system perceives color. Unfortunately, the Retinex Land-McCann original algorithm is both complex and not fully specified. Indeed, this algorithm computes at each pixel an average of a very large set of paths on the image. For this reason, Retinex has received several interpretations and implementations which, among other aims, attempt to tune down its excessive complexity. But, Morel et al. have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 9 publications
(11 reference statements)
0
23
0
Order By: Relevance
“…Even though the proposed (Fourier) implementation solves the Poisson equation over the entire domain of the image (instead of the selected sub-domain), Morel et al empirically showed that the solutions of both (the exact and the Fourier based ) implementations are perceptually equivalent outside the sub-domain for a varied set of images. In a similar direction, Limare et al [18] proposed an implementation in the Fourier domain of the Retinex 3 algorithm as a Poisson Equation with Neumann boundary conditions. The method Limare et al proposed consists in setting to zero those gradients whose modulus is below certain threshold, and then compute the image that corresponds to the modified gradient map by solving the Poisson equation.…”
Section: Review Of Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the proposed (Fourier) implementation solves the Poisson equation over the entire domain of the image (instead of the selected sub-domain), Morel et al empirically showed that the solutions of both (the exact and the Fourier based ) implementations are perceptually equivalent outside the sub-domain for a varied set of images. In a similar direction, Limare et al [18] proposed an implementation in the Fourier domain of the Retinex 3 algorithm as a Poisson Equation with Neumann boundary conditions. The method Limare et al proposed consists in setting to zero those gradients whose modulus is below certain threshold, and then compute the image that corresponds to the modified gradient map by solving the Poisson equation.…”
Section: Review Of Related Workmentioning
confidence: 99%
“…As in the previous method, we complete the processing step applying a normalization to the output. The normalization is performed by setting the mean and variance of the solution of Poisson equation to match the mean and variance of the original image, this is the same normalization performed in [18], and allows to recover the mean value of the solution (which is undefined when Fourier solver is used) and give a result that can be easily compared with the input image.…”
Section: Texture Flattening (Retinex)mentioning
confidence: 99%
“…Like in the implementation of the Retinex equation [4], the Neumann boundary condition is implicitly imposed by extending the original image symmetrically across its sides, so that the extended image, which is four times bigger, becomes symmetric and periodic. The discrete Fourier transform (DFT) permits to compute directly the Fourier coefficients of a band limited and (J, L)-periodic function u from its samples u jl on a J × L grid.…”
Section: Fourier Transform Methodsmentioning
confidence: 99%
“…This corresponds to Poisson's equation on the rectangle with vanishing Neumann boundary conditions. For the implementation details see, for example, [6]. In the present article we use Poisson equation as a procedure for recovering an image from its gradient and its average value.…”
Section: Poisson Editingmentioning
confidence: 99%